Tomato leafminer, Tuta absoluta (Meyrick, 1917) - Mujica, N.; Carhuapoma, Pablo; Kroschel, Jürgen (International Potato Center, 2022)
This chapter presents a description of the current range and damage caused by the tomato leaf miner fly (Tuta absoluta) throughout the world with a focus on Africa including risk maps for establishment and severity of infestation in various African countries based on temperature dependent phenology models developed for this pest.